Student–teachers’ perceptions about folk art and their implications for teacher education - Pitri, Eliza; Fella, Argyro; Michaelidou, Antonia (Frontiers in Education, 2025)
This study examines the perceptions of first-year university student–teachers concerning folk art. The 24 participants completed a 33-question survey assessing various dimensions: prior museum experiences, perceived cultural value, personal relevance, educational applicability, and professional utility. Findings indicate limited early exposure to folk art museums, though participants generally recognized its cultural and educational significance. While many acknowledged folk art’s role in fostering respect for heritage and valued its integration into their studies, interest in personal engagement was more varied, revealing a disconnect between socio-cultural appreciation and individual connection. Folk art was perceived as highly relevant in visual arts, history, and special education but less so in quantitative disciplines, highlighting challenges for interdisciplinary integration. The results underscore the importance of teacher education strategies that cultivate personal engagement with cultural heritage and encourage the incorporation of folk art across curricula, thereby enhancing cultural competence and pedagogical creativity among future educators.